Proyecto de Inversión para la instalación de un gimnasio de Fisioterapia en la ciudad de Loja - Morocho Ordóñez, María Rosario (2016)
The main objective of this project was to know that the investment project for the installation of a physiotherapy gym in the city of Loja, San Sebastian neighborhood urban area is feasible, the same that is oriented to meet the needs of people with physical problems motors; the service is to be provided to patients alternative treatments for muscle diseases. This work consists of four chapters the same that were developed based on each of the studies considered for the creation and installation of physiotherapy gym. The market study to Loja city, which allowed denote the existence of centers of public and private physiotherapy and physical rehabilitation that offer the service to people who need it ; surveys of 392 respondents only 280 correspond to the potential demand ; Actual demand would be 195 and 138 considered effective demand for this service. Public health institutions are strong competition for the company, but for the quality and technology to be provided in the center is expected in surveys that the reception will be good. Also it recognized that users would use the service 63 times a year. As part of the deal it was found thanks to information provided by the Internal Revenue Service (IRS) that there are 14 physiotherapy centers and 24 spas that offer therapies, becoming Indirect bidders, plus half were considered to determine the amount of services provided they give each center. The means by which the promotion and advertising will be print media, radio and television took place, concluding that the company's service is the direct marketing channel (company 6 - customer). The Technical Study proper location it will be in the streets and Catacocha Olmedo, industry San Sebastian city of Loja was analyzed; since in the surveys highlighted the needs of users from a central location where they can move without problems, and comfortable where they had the opportunity to park your car; the size of the facilities, human resources and materials are determined by the local space where it will be installed; care processes and equipment necessary for the service was quoted in Quito Abamedic and JM Medical companies. The lifetime of the investment project is 5 years It is noteworthy that the installed capacity will be 100% which will start gradually to become known in the market from 90%, 95% up to 100%. The organizational study that tried the same way on the constitution, it will be as Sole Limited Liability Company; functional and organizational structure was designed to hold the following positions: Manager-owner, Secretary, Accountant, Lawyer Physiatrists and will be required when there is a need, which will be required for the service. And the Economic and Financial Study yielded information on the requirements for the implementation of the company; for it must obtain permits and licenses based on the rules and regulations of the country; Thus it start with an investment of $ 64,877.85; plus an IRR of 46.27% was obtained; a NPV of $ 65,777.33; the benefit-cost ratio was 1.23 and Payback will be in 22 months, 27 days, 14 hours and 24 minutes; thus establishing the feasibility of the project for the implementation thereof.